2022
DOI: 10.3389/fpubh.2022.1018866
|View full text |Cite
|
Sign up to set email alerts
|

The Global Burden of Disease attributable to low physical activity and its trends from 1990 to 2019: An analysis of the Global Burden of Disease study

Abstract: IntroductionLow physical activity (LPA) is associated with several major non-communicable diseases (NCDs) and premature mortality. In this study, we aimed to assess the global burden and trends in disease attributable to LPA (DALPA) from 1990 to 2019.MethodsAnnual age-standardized disability-adjusted life years (DALYs) and death rates of DALPA [all-cause and five specific causes (ischaemic heart disease, diabetes mellitus, stroke, colon and rectal cancer, and breast cancer)] by sex, age, geographical region an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 35 publications
(41 reference statements)
0
20
0
1
Order By: Relevance
“…The association between LPA and T2DM has been widely acknowledged, and it has been found that physical inactivity contributes to 6.9% of the burden of T2DM 15 . The correlation between LPA and T2DM is further supported by the increasing prevalence of physical inactivity globally.…”
Section: Discussionmentioning
confidence: 97%
“…The association between LPA and T2DM has been widely acknowledged, and it has been found that physical inactivity contributes to 6.9% of the burden of T2DM 15 . The correlation between LPA and T2DM is further supported by the increasing prevalence of physical inactivity globally.…”
Section: Discussionmentioning
confidence: 97%
“…Globally, the number of deaths due to low physical activity have been estimated to almost reach 1 million in 2019 [ 237 ]. Nonetheless, the benefits of adequate physical activity span from cardio-metabolic outcomes to mental health, leading to an overall prolonged life and fewer years of life lost due to disability [ 238 ].…”
Section: Underrated Aspects Of the Mediterranean Dietmentioning
confidence: 99%
“…In 2019, an estimated 15.7 million disability-adjusted life years and 832,000 deaths were attributed to low physical activity globally. 1 , 2 Although extensive studies have purported the health benefits of physical activity in any form and intensity, 3 this notion is challenged by an increasing body of evidence distinguishing the health benefits associated with leisure time physical activity from occupational physical activity (OPA). The latter, at a high level of intensity, seemed to be harmful in some cases.…”
Section: Introductionmentioning
confidence: 99%